Adherence With Antihypertensive Drug Therapy and the Risk of Heart Failure in Clinical Practice. Issue 4 (October 2015) - Corrao, Giovanni; Rea, Federico; Ghirardi, Arianna; Soranna, Davide; Merlino, Luca; Mancia, Giuseppe
<x xml:space="preserve">Abstract</x> Randomized clinical trials have shown that antihypertensive treatment reduces the risk of heart failure (HF). Limited evidence exists, however, on whether and to what extent this benefit is translated into real-life practice. A nested case–control study was carried out by including the cohort of 76 017 patients from Lombardy (Italy), aged 40 to 80 years, who were newly treated with antihypertensive drugs during 2005. Cases were the 622 patients who experienced hospitalization for HF from initial prescription until 2012. Up to 5 controls were randomly selected for each case. Logistic regression was used to model the HF risk associated with adherence to antihypertensive drugs, which was measured by the proportion of days covered by treatment (PDC). Data were adjusted for several covariates. Sensitivity analyses were performed to account for possible sources of systematic uncertainty. Compared with patients with very low adherence (PDC, ⩽25%), low, intermediate, and high adherences were associated with progressively lower risk of HF, reduction in the high-adherence group (>75%) being 34% (95% confidence interval, 17%–48%). Similar effects were observed in younger (40–70 years) and older (71–80 years) patients and between patients treated with angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and diuretics. There was no evidence that adherence with calcium-channel blockers reduced the HF risk. Antihypertensive treatment lowers the HF risk in real-life practice, but adherence to treatment is necessary for a substantial benefit to take place. This is the case with a variety of antihypertensive drugs.